Social integration and mental health - a decomposition approach to mental health inequalities between the foreign-born and native-born in Sweden - Anna Brydsten; Mikael Rostila; Andrea Dunlavy (BMC, 2019)
Abstract Background The increasing mental health inequalities between native- and foreign-born persons in Sweden is an important public health issue. Improving social integration has been stressed as a key strategy to combat this development. While a vast amount of studies have confirmed the importance of social integration for good mental health, less is known about the role of different types of social integration, and how they relate to mental health inequalities. This study aimed to examine the extent to which indicators of social integration explained mental health inequalities between the native- and foreign-born. Methods Based on the Health on Equal Terms survey from 2011/2015 in Västra Götaland, Sweden (n = 71,643), a non-linear Oaxaca-Blinder decomposition analysis was performed comparing native- and foreign-born individuals from Nordic-, European- and non-European countries. The General Health Questionnaire was used to assess psychological distress, while 11 items assessed employment conditions and economic disparities, social relations, and experiences of discrimination to measure different aspects of social integration. Results Differences in social integration explained large proportions of observed mental health differences between the native- and foreign-born. Important indicators included low levels of social activity (20%), trust in others (17%) and social support (16%), but also labour market disadvantages, such as being outside the labour market (15%), unemployment (10%) and experiencing financial strain (16%). In analyses stratified by region of origin, low trust in others and discrimination contributed to the mental health gap between the native-born and European-born (17 and 9%, respectively), and the native-born and non-European-born (19 and 10%, respectively). Precarious labour market position was a particularly important factor in the mental health gap between the native-born and Nordic-origin (22%), and non-European origin (36%) populations. Conclusion Social integration factors play a central role in explaining the mental health inequality between natives and migrants in Sweden. Our findings suggest that public health actions targeting mental health gaps could benefit from focusing on inequalities in social and economic recourses between natives and migrants in Sweden. Areas of priority include improving migrants' financial strain, as well as increasing trust in others and social support and opportunities for civic engagement.